Kepatuhan Minum Tablet Zat Besi Dengan Peningkatan Kadar Hb Ibu Hamil di Puskesmas Purwoyoso Semarang - Dian Litasari; Agus Sartono; Mufnaetty - (Universitas Muhammadiyah Semarang, 2014)
Background. Anemia is a condition when the blood haemoglobin at under the normal level. Pregnant women are categorized as anemia if the blood haemoglobin less than 11 gram percent (World Health Organization, 2002) In majors anemia in pregnant women due by lack intake of iron (fe), so it’s called the Iron Nutrition Anemia. The Data in Purwoyoso Public Health Center, Semarang, depicted that during last 4 years prevalence anemia in the region that district is still high, which is 45% (2010), 41% (2011), 52% (2012) and 49% (2013). To cope the anemia of pregnant women, Purwoyoso Public Health Center has been implementing the program of distribution iron tablet to all pregnant women, 90 tablets during pregnancy. The general aim of this study is to analysis the relationship of the compliance level of drinking iron tablet with the increasing of pregnant woment’s blood haemoglobin level The data of the complients level of drinking iron tablet was collected by interviews methode and the increasing of blood haemoglobin level was collected Shahli method. Univariat Analysis were done by using frequency distribution table. The relations analysis between the compliance level of drinking iron tablet and the increasing of pregnant women’s blood haemoglobin level were done by the Rank- Sperman test. The results. Total of the pregnant women were got the number of iron tablet 90. Some of them (85.7%) acknowledging drink iron tablets. The lowest compliance level is 81% and the highest is 100 %. The average of pregnant women’s blood haemoglobin level before drinking iron tablets is 10.9 gram percent, with standard deviation 1.0486 gram percent. After dringking the iron tablets, the average of pregnant woment’s blood haemoglobin level is 11.6 percent, with standard deviation 0.35857 gram percent. There are an increasing of the level blood haemogloben, 0,7 gram percent the average. The Rank-Spearman Test expose that there was a relationship between the compliance level of drinking iron tablet and the increasing of pregnant woment’s blood haemoglobin level ((p value = 0,002<0,0,05) Conclusion There is a relationship between the compliance level of drinking iron tablet with the increasing of pregnant women’s blood haemoglobin level at Purwoyoso Pubpic Health Center, Semarang.